Effect of balance training and posture exercises on functional level in mental retardation - Kubilay, Neslihan S.; Yildirim, Yucel; Kara, Bilge; Akdur, Hulya Harutoglu (Turkey Assoc Physiotherapists, 2011)
Purpose: The aim of this study was to determine the effect of balance training and postural exercises on the functional level in individuals with mild mental retardation. Material and methods: Twenty-eight mildly mentally retarded (IQ=50-70) students who were attending the Special Education Elementary School were included for this study. Participants were randomly assigned to exercise (N=14) and control (N=14) groups. The exercise group participated in a balance training and postural exercise program with a Swiss ball for 8 weeks at a frequency of three times per week, in addition to the physical education program at the school. The control group followed only the physical education program at the school. Muscle endurance (Sit-Ups Test), flexibility (Sit and Reach Test), muscle strength and coordination (Chair Rising Test), functional mobility (Timed Up and Go Test and 50 Foot Walking Test) and balance (Pediatric Balance Scale) tests were performed to assess those variables. Assessments were performed prior to commencing the exercise program and after completion of the exercise program. Results: There was no statistically significant difference when the two groups were compared (p>0.05). A statistically significant difference was found in all parameters except flexibility in the exercise group (p<0.05). Conclusions: It was concluded that balance training and postural exercises were effective in improving the functional level in individuals with mental retardation.
Keywords: Postural balance; Mental retardation; Exercise